Journalism education in the post-truth era: an exploration of the voices of journalism students in Greece and Cyprus - Theodosiadou, Sofia; Spyridou, Lia Paschalia; Panagiotou, Nikos; Milioni, Dimitra L.; Papa, Venetia (My University, 2021)
Journalism is in a state of flux and so is journalism education. The present study engages in a comparative qualitative analysis focusing on the viewpoints of journalism students in Greece and in Cyprus regarding journalism education in the post–truth era, media literacy, and journalism quality. Drawing upon evidence from four focus groups conducted in the journalism/ communication departments of two public universities in Greece and Cyprus, the findings show highly similar attitudes between the two departments. In particular, it was found that journalism students acknowledge the need for journalists’ increased responsibility towards their publics and emphasize the necessity of (normative) skills and practices as important means in the direction of quality journalism; ICT-related journalistic skills, indepth research, specialization, impartiality and verification, topic plurality and avoidance of agenda-setting stereotypes.
Keywords: Greece; Journalism education; media literacy; quality journalism; fake news; Cyprus